4-tert-Butyl-2-(4-tert-butylpyridin-2-yl)pyridinium nitrate - Wen-Sheng Wu (Acta Crystallographica Section E, 2011)
In the title compound, C18H25N2+·NO3−, the dihedral angle between the pyridine rings is 19.06 (10)°. In the crystal, the ions are linked into a three-dimensional network by N—H...O and C—H...O hydrogen-bonding interactions.